Metal-Organic Frameworks : Applications in Separations and Catalysis - García, Hermenegildo, 1957-; Navalon, Sergio (Wiley-VCH, 2018)
Focusing on applications in separation, adsorption and catalysis, this handbook underlines the importance of this hot and exciting topic. It provides an excellent insight into the synthesis and modification of MOFs, their synthesis on an industrial scale, their use as CO2 and chemical warfare adsorbers, and the role of defects in catalysis. In addition, the authors treat such new aspects as biocatalysis and applications in photocatalysis and optoelectronic devices.
Keywords: Supramolecular organometallic chemistry.; Organometallic polymers.; Heterogeneous catalysis.; elektronické knihy; electronic books